Analysis of Conceptual Understanding of Acids and Bases: A Literature Review - Deliana Dwi Hafsari; Dania Widia Cahyani; Semilir Inas Khairani; Afridha Laily Alindra (MO.RI Publishing, 2026)
Through an analytical synthesis comparing similarities and differences across various studies, this literature review identifies research trends dominated by qualitative approaches among Grade XI students with a focus on acids and bases, as well as multilevel diagnostic instruments for student misconceptions in chemistry. The review highlights research gaps in the integration of multilevel chemical representations, acknowledges the limitations of prior studies that remain largely descriptive without comprehensive conceptual mapping, and proposes future research directions in the form of evidence-based pedagogical interventions to address student misconceptions about acids and bases. This situation is further compounded by the dominance of rote-learning methods that neglect deeper understanding at the submicroscopic level. Therefore, the instructional approach recommended is the integration of guided inquiry, which is capable of bridging students' understanding from the macroscopic to the submicroscopic perspective through technology-based simulations and laboratory experiments.